The relation between vaccination against covid-19 and mortality in brazil - Faria, Carolina; Schramm Neto, Fernando; Machado, Yuri (Brazilian Journal of Global Health, 2021)
OBJETIVO: A OMS classificou a Covid-19 como uma pandemia em março de 2020, sendo a imunização a melhor opção para prevenir sua disseminação. No Brasil, a vacinação ocorre desde janeiro de 2021. Este estudo tem como objetivo investigar se a imunização em massa contra a Covid-19 reduziu a mortalidade. MÉTODOS: Pesquisa original, quantitativa e documental. Para fundamentação teórica, foi realizada uma revisão narrativa da literatura. Os critérios de inclusão foram artigos publicados entre 2020 e 2021, nos idiomas inglês, português e espanhol. A base de dados utilizada foi a Biblioteca Virtual de Saúde, utilizando os seguintes descritores: “Vacinação”, “Eficácia”, “Mortalidade”, “Coronavírus”. RESULTADOS: A mortalidade aumentou entre fevereiro e abril, com pico de 12,86% de óbitos por milhão de habitantes. Nesse período, a chegada de novas variantes, como a Delta, e o não cumprimento das medidas de isolamento social contribuíram para que este índice permanecesse elevado. A partir de junho, as mortes por Covid-19 diminuíram continuamente. Isso está relacionado à vacinação, que passou de 12,11% no início de junho para 31,05% dos indivíduos parcialmente vacinados no final de setembro. CONCLUSÃO: A pandemia da Covid-19 é um grave problema de saúde pública. Somente em meados de abril, com a ampliação da distribuição dos imunizantes, as taxas de mortalidade começaram a cair. No entanto, não podemos minimizar o número de mortes no Brasil, que atualmente chega a 500 vítimas por dia. Assim, é necessário manter medidas de proteção e vacinação da população para que a pandemia termine. DESCRITORES: Coronavírus, Vacinação, Indicadores de morbidade e mortalidade. ABSTRACT OBJECTIVE: The WHO classified Covid-19 as a pandemic in March 2020, immunization being the best option to prevent its spread. In Brazil, vaccination has been carried out since January 2021. This study aims to investigate if mass immunization against Covid-19 has brought mortality reduction. METHODS: An original, quantitative, and documentary research. For theoretical basis, a narrative literature review was performed. The inclusion criteria were articles published between 2020 and 2021, in English, Portuguese and Spanish. The database used was the Virtual Health Library, using the following descriptors: "Vaccination", "Efficacy", "Mortality", "Coronavirus". RESULTS: Mortality rates increased between February and April, with a peak of 12.86% deaths per million inhabitants. During this period, even though population vaccination had started, the arrival of new viral variants, alike Delta, and the lack of compliance with social isolation measures contributed so that mortality remained high. From June onwards, the Covid-19 mortality rate declined continually. This is related to the increase in vaccination, going from 12.11% at the beginning of June to 31.05% of individuals partially vaccinated at the end of September. CONCLUSION: The Covid-19 pandemic is a serious public health problem, with Brazil being one of the most affected countries. Only in mid-April, with the expansion of the distribution of immunizing agents, mortality rates started dropping. However, we cannot minimize the number of deaths, which so far reaches 500 deaths per day. Thus, it is necessary to maintain protective measures and population vaccination so that the pandemic can come to an end. DESCRIPTORS: Coronavirus, Vaccination, Morbidity and Mortality Indicators.